Pendugaan Nilai Heritabilitas Bobot Lahir Dan Bobot Sapih Pada Babi Duroc Dan Yorkshire - Yuli Arif Tribudi; Ahmad Tohardi (Jurusan Produksi Ternak, Fakultas Peternakan, Universitas Brawijaya, 2018)
The research was conducted from May – September 2017 in PT Fajar Semesta Indah Singkawang. This study aims to estimate of genetic parameter on birth weight and weaning weight in Duroc and Yorkshire pig. The material used in this study were Duroc danYorkshire by the number of 286 and 2017 pig. Variables observed in this study were birth weight, weaning weight and mortality weaning. Data analysis of litter size heritability was estimated using paternal half sib method and heritability birth weight and weaning weight using nested design. The results showed the average birth weight and weaning weight in breed pig Duroc (1.22±0.22 kg and 6.52±0.98 kg) and Duroc pig (1.25±0.19 kg and 6.69±0.67 kg). Estimated heritability birth weight and weaning weight in breed pig Duroc (0.26±0.19 and 0.34±0.12) and Yorkshire (0.15±0.21 and 0.47±0.36). The heritability of birth and weaning weight were considered as high which means that the selection programme will be more effective and efficient in improving the genetic merits.